Effect of Aerobic Training on Walking Capacity and Maximal Exercise Tolerance in Patients With Multiple Sclerosis: A Randomized Crossover Controlled Study - Rampello, Anais; Franceschini, Marco; Piepoli, Massimo; Antenucci, Roberto; Lenti, Gabriella; Olivieri, Dario; Chetta, Alfredo (Physical therapy, 2007)
Physical deconditioning is involved in the impaired exercise tolerance of patients with multiple sclerosis (MS), but data on the effects of aerobic training (AT) in this population are scanty. The purpose of this study was to compare the effects of an 8-week AT program on exercise capacity-in terms of walking capacity and maximum exercise tolerance, as well as its effects on fatigue and health-related quality of life-as compared with neurological rehabilitation (NR) in subjects with MS. Nineteen subjects (14 female, 5 male; mean age [X+/-SD]=41+/-8 years) with mild to moderate disability secondary to MS participated in a randomized crossover controlled study. Eleven subjects (8 female, 3 male; mean age [X+/-SD]=44+/-6 years) completed the study. After AT, but not NR, the subjects' walking distances and speeds during a self-paced walk were significantly improved, as were their maximum work rate, peak oxygen uptake, and oxygen pulse during cardiopulmonary exercise tests. The increases in peak oxygen uptake and maximum work rate, but not in walking capacity, were significantly higher after AT, as compared with after NR. Additionally, the subjects who were most disabled tended to benefit more from AT. There were no differences between AT and NR in effects on fatigue, and the results showed that AT may have partially affected health-related quality of life. The results suggest that AT is more effective than NR in improving maximum exercise tolerance and walking capacity in people with mild to moderate disability secondary to MS.